Migration in South Africa: Conflicts and Identities. Eddie M. Rakabe and Chris C. Nshimbi: Review by Alan Hirsch - Hirsch, Alan (New Agenda: SA Journal of Social and Economic Policy, 2025)
Eddie Rakabe and Chris Nshimbi have assembled an interesting collection of chapters dealing with the broadly common theme of the complexity of responding to and managing migration in South Africa today. Some of the chapters are essays, contesting ideas in the context of existing knowledge, while others add to the stock of knowledge itself, presenting on original research. The sudden influx into South Africa of Zimbabwean migrants in 2008 and 2009 and the emergence, in the same period, of virulent anti-migrant rhetoric and violent anti-migrant actions brought the issue of migration policy to the fore. Since then, it has seldom been out of the frame of South African politics.